Bibliometric: Halal Brand on Marketing Performance - Tikawati, Tikawati; Hudayah, Syarifah; Abidin, Zainal; Rahmawati, Rahmawati (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2024)
The rapid development of the halal industry has positioned halal branding as a critical element in influencing consumer behavior and shaping marketing strategies. In the increasingly competitive global market, halal labeling and brand image significantly shape consumer trust and preferences, which subsequently impact a company's marketing performance. Despite its importance, research on how halal brands affect marketing performance remains limited. This study conducted a bibliometric analysis of halal brands and marketing performance by reviewing previous studies indexed in the Scopus database from reputable international journals. Using quantitative methods, the collected data provides a comprehensive overview of outputs, organizations, authorship, and topic characteristics, demonstrating the feasibility of bibliometric analysis. The research focuses on articles published between 2012 and 2022, utilizing search engines such as Google Scholar, Scopus, Elsevier (Science Direct), and Publish or Perish. Results show a growing academic interest in the relationship between halal brands and marketing performance, indicating the need for further research to deepen understanding in this area.